Gizi buruk anak di RA Zainul Ulum Bantur Malang - Pratama, Marlendra Arif (Maliki Interdisciplinary Journal, 2023)
Nutrition is an organism's process of using food to be consumed normally through the process of digestion, absorption, transportation, storage, metabolism and excretion of nutrients to maintain life, growth and normal function of organs and to produce energy. In Indonesia the prevalence of malnutrition is still increasing. Susenas results show a decrease in the prevalence of malnutrition under five, from 10.1% in 1998 to 8.1% in 1999 and to 6.3% in 2001. However, in 2003 and again increased to 8.8% in 2005. Based on reports from the Health Office throughout Indonesia, there was a decrease in cases of malnutrition in 2005, with 76,178 cases recorded, then decreased to 50,106 cases in 2006 and 39,080 cases in 2007. The research method used is the case study method which is part of the of qualitative methods. This research was carried out at RA ZAINUL ULUM BANTUR MALANG. The time of research is October to early December 2021. The population and sample in this study are 5 children.